Marketing Strategies to Increase Consumer Purchase Interest at Nao-Mi UMKM in Gorontalo - Sitti Husna Noviana Djou; Rahayu Agustina Ishak (Journal of Governance and Global Studies, 2025)
This community service activity aims to increase consumer purchasing interest by providing marketing strategy assistance to Nao-Mi MSMEs in Gorontalo. The main problem faced by partners is the suboptimal implementation of marketing strategies that are adaptable to changes in consumer behavior and the development of marketing media. The service method uses a participatory approach that places MSME actors as active subjects in all stages of the activity, from problem identification, planning, implementation of marketing assistance, to evaluation. The mentoring focused on strengthening understanding of marketing concepts, marketing strategy planning, and improving consumer-oriented marketing communication skills. The results of the activity show an increase in the understanding and awareness of MSME actors regarding the importance of planned and sustainable marketing strategies in attracting consumer purchasing interest. Additionally, the participatory approach encourages business owners to be more reflective and responsive to market dynamics, enabling them to manage marketing more independently. This activity makes a practical contribution to the development of MSMEs and strengthens the role of community service in supporting the improvement of local business competitiveness.